Comparative study between microscopic and endoscopic stapes surgery - Harikumar, B.; Arun Kumar, K. J. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: To investigate whether endoscopic stapes surgery is safer and less invasive than conventional stapes surgery using an operating microscope. Methods: The subjects were 60 patients who were divided consecutively into group A undergoing microscopic stapedotomy and group B undergoing endoscopic stapedotomy. The procedures for endoscopic surgery were fundamentally the same as those for microscopic surgery, except for post aural incision used in some patients in microscopic group. The two surgical techniques were compared with respect to the operating time, approach, drilling of posterosuperior canal, manipulation of chorda tympani, visualisation of anterior crus, postoperative hearing, postoperative pain, and complications. Results: There were no differences of operating time or postoperative hearing between the endoscopic and microscopic groups. There was very little postoperative pain in the endoscopic group. Drilling at the posterosuperior part of the external auditory canal was less extensive in the endoscopic group than in the microscopic group. Visualisation of anterior crus of stapes was good in endoscopic group. Conclusions: Endoscopic stapes surgeries are technically feasible, safe and promising. The main advantages were: easy access, virtually no trauma to the chorda tympani nerve and excellent vision. The disadvantages were the lack of stereoscopic vision, having to work with one hand only and the learning curve.